Assessment of variability in the root system characteristics of banana (Musa spp.) according to genome group and ploidy level - Blomme, Guy; Swennen, Rony L.; Tenkouano, A. (2000)
The relative contribution of ploidy status and genome composition to the variability of root traits in Musa was studied in 18 genotypes (from 5 genomic groups and 3 ploidy levels) at Onne, Nigeria. There was a significant effect of ploidy level on the different characteristics, except for root dry weight and cord root length of the mat. Generally, with increasing ploidy level the magnitude of plant characteristics tended to increase. The effect of genotype was significant for all assessed traits, while the effect of genome group was significant for all shoot and several root traits. There was an increase in sucker development with decreasing ploidy level. All diploid bananas had a non-regulating suckering behaviour resulting in a faster cycling, while triploids and tetraploids had a regulated or an inhibited suckering. There was a clear relationship between shoot and root growth according to genome group.